High performing, high poverty public secondary schools a model for educational management - Termulo, Mary Grace Sanchez (2005)
The primary inquiry was on inferring an educational management model of high performing public secondary schools in the high poverty areas of Luzon. Results revealed that achievement test results are still the primary means of measuring school performance; however peer accreditation adds to school improvement and school quality. The model of educational management was characterized by shared goals, inclusivity, efficacy, sense of family, collaboration, communication, transparency, commitment, effective school leadership, use of standards, strict monitoring of teaching, focus on students, and sourcing out.
Thesis (Ph.D. Educational Administration)--University of the Philippines Diliman.
Keywords: School management and organization -- Philippines -- Luzon; High schools -- Philippines -- Luzon -- Administration; Academic achievement -- Philippines -- Luzon